Approches, concepts et thématiques en histoire des femmes et du genre au XXIe siècle dans la revue Genre & Histoire - Michelle Zancarini-Fournel; Camille Noûs (Genre & Histoire)
The inventory of research into the history of women and gender, done by means of the abstracts of theses published in Genre et Histoire, shows that themes concerning the body, sexualities and violence, and feminisms have been favoured as well as approaches which mix gender and class, gender and commitment or gender and religions. Research into identities and their political social and cultural consequences should be the ones that are developed in the future.